O logos ontológico fundante da potencialidade ética no devir em Heráclito - Nascimento, Márcio José Orofino do (2024)
The fact that the philosopher of the logos was concerned with social order is evidenced not only by the surviving fragments but also by the doxography about him that has come down to us. Heraclitus, also known as the philosopher of fire, can be placed between two views of his time (6th century B.C.): a popular (or mythical) one, which he participates in by referring to a natural (divine) law, a source of inspiration for human laws, which are pale reflections of that; and a scientific orientation, of which he was also a precursor, for example, with the theories of the unity of opposites and becoming. Based on Heidegger's exposition in the course “Logic. Heraclitus’ Doctrine of the Logos”, from the summer semester of 1944, we aim to approach what this German thinker calls “original logic”, that is, that which, originally, concerns the thinking of the Λόγος, that is, the original Λόγος which, thought, becomes present in thinking itself. This was the case with Heraclitus' thinking. We then return, guided by Heidegger, to the dawn of ancient philosophy, in search of an essential dialogue between thought and being in its original sense, which underlies every manifestation of the human spirit in deciphering its meaning, which emerges in natural unveiling. Therefore, the simple purpose of Heidegger's reading of the logos in Heraclitus is to meditate on what the Ephesian says about the logos, subsequently articulating some of his fragments in which he directly and indirectly addresses the logos, which “distinguishes” itself between the human and the original (common), and which accounts for the possibility of knowledge and the (potential) autonomy of the human being, and the consequent unfolding of an ethos (an ethics) aligned with the unity of cosmic diversity as will be shown. Certain readings of Heraclitus' theory of becoming could lead to the non-sanctioning of the possibility of knowledge in Heraclitus (and, therefore, of the possibility or potentiality of ethics in his doctrine). Hence, our concern in showing that this is not the case. Finally, we embark on the study of ethos in Heraclitus – that is, the proper way of being of man, which originally meant shelter, a way of inhabiting, indicating the proper, essential, and original way of manifesting man's being in the world – based on the study of the ontological principles of the human condition that, structuring man's ethos, refer to the truth of being. In short, we mainly seek to understand how Heraclitus, by thinking the logos, reveals a social and ethical order that aligns with cosmic unity, exploring his maxims and fragments, and how this translates into the possibility of human knowledge and autonomy, culminating in the analysis of ethos, the proper manifestation of human being in the world, grounded in the truth of being (that is, in the common logos).